Taxation and public spending efficiency : an international comparison - Afonso, António (2019)
This paper evaluates the relevance of the taxation for public spending efficiency in a sample of OECD economies in the period 2003-2017. First, we compute the data envelopment analysis (DEA) scores and the Malmquist productivity index to measure the change in total factor productivity, the change in efficiency and the change in technology. Second, we explain these newly computed public efficiency scores with tax structures using a reduced-form panel data regression specification. Looking at the period between 2007 and 2017, our main findings are as follows: inputs could be theoretically lower by approximately 32-34%; the Malmquist indices show an overall decrease in technology and in TFP. Crucial for policymaking, we find that expenditure efficiency is negatively associated with taxation, more specifically direct and indirect taxes negatively affect government efficiency performance, and the same is true for social security contributions.